PENGARUH APLIKASI KOMPOS KOTORAN KAMBING DENGAN RESIDU UREA-HUMAT TERHADAP UNSUR P, K SERTA PERTUMBUHAN OKRA (Abelmoshus esculentus L.) PADA ENTISOL, WAJAK MALANG - Cahyo Bagus Susanto; Syahrul Kurniawan (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Entisol of Wajak Malang has low base saturation and organic matter and slightly acid. The result of the analysis also showed that soil has nutrient P with high criteria; however, N, K, Ca, Mg, Na contents are low to very low criteria. Application of humic acid at the first planting can leave residual nutrients and can still be used in the second planting. Besides urea-humic, goat manure can also be because it can improve soil properties, organic matter and nutrients contents. The purpose of this study was to explore the effect of the application of urea-humic residue with goat manure on the availability of phosphorus, potassium and the growth of okra on an Entisol of Wajak Malang. The combination of treatments consisted of: U1 (soil residue urea-humic 100% + goat manure), UH1 (soil residue of urea-humic 75% + goat manure), UH2 (soil residue of urea-humic 100% + goat manure), UH3 (soil residue of urea-humic 125% + goat manure), UH4 (soil residue if urea-humic 150% + goat manure). The five treatments were arranged in a completely randomized design with three replicates. The results showed that urea-humic residue with application goat manure had no significant effect on available P, exchangeable K in the soil, plants height and leaf number of okra on 4, 6 and 8 weeks after planting.